Direct Synthesis of Disubstituted 3‐Isoquinolinone Derivatives through the Construction of C−N, C=O, and C(sp2)−C(sp3) Bonds under Transition‐Metal‐Free Conditions. Issue 3 (30th December 2022) - Shi, Jianyi; Chen, Xia; Huang, Jingyun; Lu, Yantong; Yang, Zhendong; Zhong, Mingli; Zhu, Zhongzhi; Chen, Xiuwen
Abstract: The efficient three‐component cascade coupling reaction of 3‐haloisoquinolines, haloalkanes, and sp 3 ‐carbon nucleophiles (acetophenone or nitromethane) led to a series of structurally novel 1, 2‐disubstituted‐3‐isoquinolinones through the formation of C(sp 3 )−C(sp 2 ), C−N, and C=O bonds. The NaOAc‐promoted reaction described in this work is simple to operate, environment friendly, and highly selective. Abstract : A one‐step construction of C−N, C=O and C(sp 2 )−C(sp 3 ) bonds under transition‐metal‐free conditions for the synthesis of disubstituted 3‐isoquinolinone derivatives is reported. The reaction is characterized by wide substrate scope, high selectivity and environmental friendliness.